The Institutional Roles of the Bandung Branch of Indonesian Orchid Association in Orchid Agribusiness Development - Muhammad As’ad Ansharullah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2021)
The purpose of this study was to determine the extent of the institutional role of the Indonesian Orchid Association in orchid agribusiness development in Bandung Regency. The research method used was a survey. The number of respondents was taken using purposive sampling. Data were analyzed by using descriptive in the form of scores. The results of this study state that the Indonesian Orchid Association (PAI) as an institution plays a role in the development of orchid agribusiness in Bandung, especially in the procurement of production facilities, farming, marketing, and supporting agribusiness. For the assessment score of the institutional role of the Indonesian Orchid Association (PAI) on the development of orchid agribusiness, two answers were given in a closed yes and no equipped with answers openly by the respondents. The results of this study state that the Bandung branch of the Indonesian Orchid Association as an institution plays a role in the development of orchid agribusiness in Bandung especially in the procurement of production facilities, farming, marketing, and supporting agribusiness. Suggestions to the Indonesian Orchid Association (PAI) to ease in carrying out the institutional roles of the Bandung branch of PAI; the Bandung branch of the PAI should divide into three parts, namely PAI of Bandung City, PAI Bandung Regency, and PAI West Bandung Regency.